Keaktifan Mengikuti Layanan Informasi Bidang Bimbingan Sosial Siswa Di Sekolah Menengah Atas Negeri 12 Pekanbaru - Nur Wisma; Suci Habibah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research aims to see the activeness of exploring information services in the social sector of SMA Negeri 12 Pekanbaru students. This research is a quantitative descriptive research. The research population was all students of class XI, amounting to 347 people. . Sampling the authors drew 15% of the population with the Proportional Random Sampling method. Data were collected using a questionnaire and documentation. To see the objective of exploring student social field data services, the percentage was descriptively analyzed. After the information obtained in the field was analyzed, it was concluded that student activity in exploring social data services in SMA Negara 12 Pekanbaru was categorized as active. These results were obtained from the percentage of answers to the questionnaire which was 78.91%.